Climate Risk Management in Agricultural Extension Mainstreaming for Zambia’s Higher Education System - Hansen, James; Dinku, Tufa; Grossi, Amanda; Kasoma Pele, Winnie; Makungwe, Mirriam; Sinachikupo, Kenneth (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project aims to improve access to climate information services and climate-smart agriculture (CSA) technologies to enhance agricultural resilience in Africa. A key focus is strengthening agricultural extension and advisory services (EAS) in Zambia and five other target countries by co-designing curricula to build capacity in managing climate risks. These curricula empower EAS providers to use localized climate information and tools in their work with farmers, to foster agricultural resilience.In 13-15 November 2024, a workshop convened representatives of Zambian higher education institutions (universities and ATIs), national government, and AICCRA technical partners (IRI, Alliance of Bioversity and CIAT, and IWMI) at The Urban Hotel, Lusaka, to develop and endorse an action plan for integrating the Climate Risk Management in Agricultural Extension (CRMAE) curriculum within Zambia’s higher education system. This report summarizes the workshop process and outcomes.